Beyond Profit: How Board Gender Diversity Shapes Financial and ESG Performance in Indonesia - Maharani, Nadya (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
: This study examines the impact of board gender diversity, board size, and the presence of a critical mass of women on corporate boards on both financial and ESG performance in Indonesian publicly listed firms between 2020 and 2024. Using a fixed effects panel regression on a balanced dataset of 51 firms observed over five years, the analysis reveals a nuanced relationship between governance structures and firm outcomes. The results show that board gender diversity has a positive and significant effect on ESG performance, supporting the argument that female directors contribute perspectives that enhance corporate responsibility. However, the critical mass hypothesis is not supported, indicating that numerical thresholds alone are insufficient to drive change. Board size is positively and significantly associated with both ESG performance and Tobin’s Q, while neither gender diversity nor board size has a measurable impact on accounting-based indicators such as ROA and ROE. These findings challenge the universal applicability of Critical Mass Theory, suggesting that its influence may be constrained in emerging markets such as Indonesia, where cultural and institutional factors limit the effectiveness of female representation. Overall, the study contributes to the governance–performance literature by demonstrating that the benefits of board diversity are context-specific and vary across performance measures.